Konsep dan Fungsi Amtsāl Al-Qur’an Menurut Jalaluddin as-Suyuthi dalam Al-Itqān fī ‘Ulūm al-Qur’ān - Sukhulil Jannah; Wildan Setiawan (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study examines the concept of amtsāl (Qur’anic parables) according to Jalaluddin as-Suyuthi in Al-Itqān fī ‘Ulūm al-Qur’ān, focusing on its definition, classification, objectives, and functions. Employing a qualitative library research approach, this study analyzes primary data from Al-Itqān and relevant classical and contemporary works on ‘ulūm al-Qur’an. The findings indicate that amtsāl serves as a rhetorical and pedagogical method to concretize abstract meanings through analogy, making Qur’anic messages more accessible and impactful. As-Suyuthi classifies amtsāl into amtsāl al-muṣarraḥah (explicit parables) and amtsāl al-kāminah (implicit parables), while some scholars recognize a third category, amtsāl al-mursalah. Although his treatment reflects a descriptive and encyclopedic approach, it provides a systematic foundation for understanding Qur’anic parables. The study concludes that the concept of amtsāl in Al-Itqān remains methodologically relevant for contemporary Qur’anic interpretation, particularly in highlighting its communicative, moral, and spiritual dimensions.